Keratinocyte Biology Structure and Function in the Epidermis - Komine, Mayumi (IntechOpen, 2022)
Keratinocytes have various functions to maintain epidermal homeostasis. Many inflammatory skin diseases can develop due to suppressed or defective anti-inflammatory properties of keratinocytes. This book discusses the structural, biological, and molecular aspects of keratinocytes. Chapters discuss keratins and attachment molecules and their importance in maintaining epidermal homeostasis, skin diseases such as psoriasis and atopic dermatitis, and aging and skin regeneration.